1988
DOI: 10.2136/sssaj1988.03615995005200060030x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Annual Manure Applications Increase Soil Organic Matter and Nitrogen, and Decrease Carbon to Nitrogen Ratio

Abstract: The effects of long‐term annual applications of cattle (Bos taurus) feedlot manure on the accumulation, decomposition (amounts and rates), and movement of organic matter (OM) and Kjeldahl‐determined N (total N) in soil were determined. Manure was applied annually since 1973 at three different levels to nonirrigated and irrigated Dark Brown Chernozemic (Typic Haploborolls) clay loam soil. Significant increases in soil OM and total N content in the first 8 and 6 yr, respectively, as affected by the level of manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(79 citation statements)
references
References 0 publications
1
75
0
3
Order By: Relevance
“…Therefore, conservation, reduced tillage, and no tillage can be effective means of mitigating CO 2 emissions from cultivated lands (Paustian et al 1997;Robertson et al 2000). Crop residue incorporation can also beneficially affect soil C accumulation through redistribution of atmospheric CO 2 to the soil (Sommerfeldt et al 1988;Lal 1997). For TOC accumulation at M39-OF, rye incorporation may play a more important role than no till, as the annual TOC accumulation was negative in M1F-OF, even though M1F-OF was also under no-till.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, conservation, reduced tillage, and no tillage can be effective means of mitigating CO 2 emissions from cultivated lands (Paustian et al 1997;Robertson et al 2000). Crop residue incorporation can also beneficially affect soil C accumulation through redistribution of atmospheric CO 2 to the soil (Sommerfeldt et al 1988;Lal 1997). For TOC accumulation at M39-OF, rye incorporation may play a more important role than no till, as the annual TOC accumulation was negative in M1F-OF, even though M1F-OF was also under no-till.…”
Section: Discussionmentioning
confidence: 99%
“…Also reported in the same study were increased OM content and decreased bulk density (Sommerfeldt and Chang 1985;Sommerfeldt et al 1988), no effect on infiltration rate and saturated hydraulic conductivity (Sommerfeldt and Chang 1986), increased acidity (Chang et al 1990), and an increase in available P (Chang et al 1991).…”
mentioning
confidence: 66%
“…Previous research in the Canadian Prairies has shown positive effects on crop yield and soil quality from manure application, and manure was found to be the best amendment to restore deteriorated/eroded soils containing low organic matter and poor crop yields [27,[34][35][36][37][38]. Similarly, the highest increase in TOC and TON from compost than other amendments in our study was due to its dual effect by directly contributing to organic C and N, plus additional indirect contri ution of C from increased b crop residue (roots, stubble, straw, chaff/fallen leaves) returned to the land/soil, as evidenced by greatest increase in straw yield in this treatment [39].…”
Section: Soil Organic C and Nmentioning
confidence: 99%